Peningkatan Voluntarty Tax Compliance dan Kinerja Direktorat Jenderal Pajak - Dwi Sulistiani; Yona Octiani Lestari (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
This study aimed to compare the tax revenue between before and after the implementation of Government Regulation No. 46 In 2013, and knowing the efectiveness of voluntary tax compliance’ increase tax-payer for SMEs. The study was conducted by using a mixed method in which for the first goal using different test methods of quantitative premises while the second goal using qualitative descriptive method to illustrate the effectiveness of the regulation. The results showed that the tax revenue after the implementation of the regulation indeed there is a greater difference than before the implementation of these regulations. The second result shows that the application of the regulation is less effective in the first 5 months of implementation.